A Comprehensive Review on Rubella Virus: Review Article (Journal of Pharma Insights and Research, 2024)
Rubella, colloquially known as German measles, is an exceptionally contagious viral illness that primarily affects children and non-immune young adults. While the infection is typically mild and self-limiting in most cases, rubella virus infection during early pregnancy can have devastating consequences, leading to a range of severe birth defects collectively termed congenital rubella syndrome (CRS). The etiological agent, Rubella virus (RV), is an enveloped, positive-sense single-stranded RNA virus and the sole member of the genus Rubivirus within the Matonaviridae family. Despite the availability of an effective and safe rubella vaccine, the disease continues to pose a significant global health threat, with an estimated 100,000 cases of CRS occurring annually worldwide, predominantly in regions with suboptimal vaccination coverage. This comprehensive review delves into the intricate details of rubella virus, encompassing its epidemiological patterns, modes of transmission, and the complex pathogenic mechanisms underlying congenital rubella syndrome